The Effectiveness of AI-Based Applications in Improving EFL Learners’ Vocabulary and Grammar Mastery: A Literature Review - Ni Putu Ritra Trees Ari Kartika Hadi Saraswati; Ni Kadek Herna Lastari (Lembaga Penelitian dan Pengabdian Masyarakat, Universitas Pahlawan Tuanku Tambusai, 2026)
This literature review explores the theoretical foundations and existing studies on the effectiveness of artificial intelligence (AI)-based applications in improving vocabulary and grammar mastery among English as a Foreign Language (EFL) learners. With the growing integration of AI in education, particularly in language learning, it becomes essential to understand how AI tools such as Grammarly, ChatGPT, Duolingo, and ELSA Speak contribute to enhancing learners’ linguistic competence. The study synthesizes existing literature and theoretical frameworks, including constructivist learning theory, the cognitive load theory, and the interactionist perspective, to analyze how AI-based tools facilitate vocabulary acquisition and grammatical accuracy. The findings from prior studies indicate that AI applications provide personalized feedback, immediate correction, and adaptive learning paths, which significantly enhance learner engagement and autonomy. However, the review also highlights limitations, such as overreliance on technology, lack of contextual learning, and potential inaccuracies in AI feedback. This paper concludes that while AI-based applications have strong theoretical and empirical support for improving vocabulary and grammar mastery, their effectiveness depends on guided implementation and integration with pedagogical strategies.